An Intervention to Promote Positive Teacher–Student Relationships and Self-Determination Among Adolescents With Emotional Disturbance. (August 2017) - Lind, John; Poppen, Marcus; Murray, Christopher
Positive teacher–student relationships provide adolescents with disabilities the confidence to explore new challenges in and out of the classroom. Goal-setting and self-determination skills have been consistently shown to promote healthy transition adjustment among students with disabilities. Despite the growing awareness of the importance of positive teacher–student relationships and self-determination, there is a paucity of specific strategies designed to improve teacher–student relationships while supporting self-determination for adolescents with high-incidence disabilities. This practitioner-focused article describes the Adolescent Goal-Setting Intervention (AGSI) and how it can be implemented in an educational context to promote teacher–student relationships and self-determination.